Response of rhizosphere microbial community structure and production performance of corn and soybean to belt planting mode - Wang, Guihua; Feng, Shilin; Han, Xiaodong; Zheng, Hui; Bai, Chunhua; Li, Guoqing; Zhao, Guofen (Frontiers in Sustainable Food Systems, 2024)
The strip planting of soybean and corn fully utilizes the root characteristics and plant height differences of soybean and corn, which can not only improve crop photosynthesis and nutrient absorption, but also fully leverage the marginal effects of corn. To investigate the response of rhizosphere microbial community structure and production performance of corn and soybean to strip planting mode and their correlation, this study was conducted at the experimental base of the Agricultural and Animal Husbandry Science Research Institute in Xing'an League, Inner MongoliaThe rhizosphere soil of Zhonglian Soybean 1505 and Tianyu 108 maize under different planting modes were studied. High throughput metagenomic sequencing technology was used to analyze the diversity and community structure of rhizosphere microorganisms in maize and soybean under modes1, 2, and 3, their production characteristics were measured for correlation analysis between the two. To provide theoretical basis for strip planting of corn and soybeans and soil health, and to achieve sustainable development of agriculture.The results showed that the planting mode had a greater impact on rhizosphere bacteria and viruses than on fungi. In the Mode 3, the microbial diversity in the rhizosphere of corn is the smallest, while the microbial diversity in the rhizosphere of soybean is the highest.The microbial community structure varies to varying degrees in different growth stages and planting modes. The dominant bacterial phyla are Pseudomonas, Actinobacteria, Bacteroidota, and Myxococcota, among others. The dominant genera of bacteria are all Bradyrhizobium, Sphingomonas, Rhodanobacter, and Pseudomonas. There are differences in the functions of carbohydrate and amino acid metabolism. In the Mode 3, the yield of corn is significantly lower than the other two modes, while the yield of soybean is the opposite. The Modes1 and 2 are beneficial for corn production, while the Mode 3 is beneficial for soybean production. S_Massilis_putida is significantly positively correlated with Corn yield. S_ lysobacter_capsici shows a highly significant positive correlation with the number of plants per square meter and the number of plants per 2 square meters of soybeans. which are expected to become biological fertilizers.